University of Florida Potato Variety Trials Spotlight: ‘Yukon Gold’ - Mario H.M.L. Andrade; Rodrick Z. Mwatuwa; Christian T. Christensen; Pam Solano; Lincoln Zotarelli (EDIS, 2021)
‘Yukon Gold’ is a fresh market potato variety selected from the progeny of a cross between W5279-4 and ‘Norgleam’ and tested under the pedigree G6666-4Y. It was released jointly by Agriculture Canada and Ontario Agricultural College, University of Guelph, Canada in 1981. In Florida, ‘Yukon Gold’ demonstrates high yield and good tuber characteristics compared to the commercial standard ‘La Chipper’. Tuber production and quality results provided in this publication are from Florida Potato Variety Trials conducted at the UF/IFAS Hastings Agricultural Extension Center between 1999 and 2019.